A Complementary Mechanism of Bacterial mRNA Translation Inhibition by Tetracyclines - Barrenechea V. (2021)
We are very thankful to Marcos Milla for donating equipment that was used in this study and others. We particularly thank Andrey Konevega and his team for providing the tRNAs that were used in this study. Also, we would like to thank all lab members of the Mil?n and Quiliano groups for their help, support, and fantastic working atmosphere. Funding. This work was supported by grants from the Peruvian Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica (154-2017-FONDECYT) and (036-2019-FONDECYT-BM-INC.INV) to PM and (406-2019-FONDECYT) to MQ and the Inn?vate Per? program (297-InnovatePeru-2016) to PM. Funding for open access was provided by the Universidad Peruana de Ciencias Aplicadas (C-014-2020).